(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Introduction: Misoprostol regimens for the induction of labor in second and third trimester IUFDs, in different doses range from 50 to 400mcg are all clinically effective. Larger doses of misoprostol potentially have an increased risk of adverse effects. If low dose of vaginal misoprostol have similar effectiveness than a higher dose used on its own, lower dose will impose dual benefit on patient in terms of less cost/risk of adverse effects. Objective: To evaluate safety and efficacy of different doses of misoprostol in termination of IUD cases during the period from January to December, 2011 in the dept. of obs and gynae, BSMMU and Khulna Medical College Hospital. Materials & Methods: A randomized control trial was conducted with sixty IUD primi or multigravida cases having 28 to 42 weeks or more gestation, singletone pregnancy and Bishops score 5 or less were included. Grand multiparas, women having history of previous caesarean section or myomectomy, transverse lie, placenta praevia were excluded from the study. The selected patients were randomly divided into two groups for termination using two different doses of misoprostol. Among 60 patients 30 (group -1) received 50mcg of misoprostol 6 hourly and 30 patients received (group -2) 100mcg of misoprostol 8 hourly per vaginally. Outcome variables: Induction delivery time, number of delivery within 24 hours, mode of delivery, side-effects and complications of misoprostol were recorded. Pulse, BP, Temperature were noted every 4 hourly. Result: Induction delivery time, mean+SD was 21.7±9.47 and 26.17±11.17 hours respectively in group-1 and group-2, (P=0.10). Number of doses required was, mean±SD 2.67±0.9 in group-1 and 2.08±0.81 in group-2, the difference was statistically significant (P<0.006). Delivery within 24 hours occurred in 20(66.67%) cases in group-1 and in 16(53.33%) in group-2. Nausea, vomiting were present 16.67% and 10% in group-1 and 33.33% and 16.67% in group- 2 respectively. In both groups most of the cases had no side effect. In group-1 there was hyperstimulation in 2(6.67%) cases and tachysystole in 1(3.33%) case. In group-2 hyperstimulation and tachysystole developed in 4(13.33%) and 2(6.67%) cases respectively. Conclusion: Both50mcg and100mcg intravaginal misoprostol are safe and effective in termination of intrauterine foetal death Bangladesh J Obstet Gynaecol, 2013; Vol. 28(1) : 15-20